2012
DOI: 10.1371/journal.pone.0029109
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Vision Training Improves Batting Statistics for University of Cincinnati Baseball Players

Abstract: PurposeBaseball requires an incredible amount of visual acuity and eye-hand coordination, especially for the batters. The learning objective of this work is to observe that traditional vision training as part of injury prevention or conditioning can be added to a team's training schedule to improve some performance parameters such as batting and hitting.MethodsAll players for the 2010 to 2011 season underwent normal preseason physicals and baseline testing that is standard for the University of Cincinnati Athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 11 publications
3
99
1
Order By: Relevance
“…It means that significant changes were observed among all participants. The number of head movements in the control group increased by 6% compared to the initial test; this result was in agreement with the previous study results which had shown an increase of 8% (17).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It means that significant changes were observed among all participants. The number of head movements in the control group increased by 6% compared to the initial test; this result was in agreement with the previous study results which had shown an increase of 8% (17).…”
Section: Resultssupporting
confidence: 93%
“…According to previous studies, good and bad performance in this test is associated with good or bad functional performance of prefrontal cortex (17).…”
Section: Methodsmentioning
confidence: 72%
“…7,8 Subjects were asked to perform 3 trials of single-leg stance on their dominant limbs for 10 seconds with EO, EC, and SV, created by a specialized eyewear (Nike SPARQ Vapor Strobes, Nike Inc, Beaverton, OR, USA), known as stroboscopic glasses that intermittently cycled between opaque and transparent for 100 millisecond periods (reducing visual feedback by half), which has been previously described. 9 Balance testing was performed on both a firm force plate…”
Section: Methodsmentioning
confidence: 99%
“…Whilst effects on motor performance are less researched, a pilot study by Mitroff et al (2013) showed a considerable increase in ice hockey shooting and passing performance for individuals who underwent SVT, whilst a control group saw no such improvements. Other studies have incorporated SVT as one of multiple tools in a visual training programme and found significantly increased baseball batting metrics (Clarke et al 2012) and significantly reduced concussion incidence (Clarke et al 2015). Appelbaum and Erickson's (2016) review of sports vision training techniques provides more detail on some of these studies.…”
Section: Introductionmentioning
confidence: 99%